The study of indicators of the functional state of the tactile analyzer in children of secondary school age with visual impairment - Liliana Riadova (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the indicators of the functional state of the tactile sensory system in the middle-school students with the visual impairments. Material and methods: indicators of the tactile sensitivity were determined by the method of the esthesiometry. In the study involved the pupils of the middle classes with the visual impairments of the community establishment «Kharkov Special Boarding School I-III degree No 12» of the Kharkov Regional Council for children with the visual impairments. Results: the considered indicators of the tactile sensitivity the 3rd phalanx the middle finger of the arm and of the middle palm in the middle school children with the visual impairments. Conclusions: it was revealed that the best indicators of tactile sensitivity on the 3rd phalanx of the middle finger of the arm were observed in boys of the 10th and girls of the 7th grade; of the middle of the palm - in boys of the 6th and girls of the 9th grade.